Fabrication of a yeast microcapsule platform for bone tissue regeneration - Oliveira, Patrícia Gaspar de (2023)
Bone is considered a mechanical support system of the human body, which imparts protection for internal organs, being also a reservoir of minerals. During life, bone tissue remains in constant remodelling and has the capacity to regenerate small lesions. Nevertheless, in situations of critical bone fractures and/or chronic diseases, endogenous bone regeneration is limited and generally results in non-union of the fracture fragments and in loss of tissue function. Bearing in mind that the improvement in life-expectancy is accompanied with a higher incidence of bone defects, it is urgent the development of biomaterials, which can deliver proosteogenic drugs or be able to instruct the differentiation of adult stem cells into progenitor bone cells. Given this, hydrogels have been increasingly explored as a tridimensional (3D) platform for support and delivery of stem cells to bone tissues, due to their permeability and similarities to the extracellular matrix (ECM). However, as a result of their high permeability, hydrogels have a low capacity for drug delivery. Yeast microcapsules (YMCAPs) have been mentioned as alternatives with the potential to encapsulate, transport and deliver therapeutic agents in a specific and localized manner. These microcapsules can be obtained through the reuse of spent yeasts discarded as a by-product of brewing industry. In this dissertation, it was aimed to obtain YMCAPs from the brewer’s spent yeast Saccharomyces pastorianus and promote their inclusion into a 3D hydrogel, through a photocrosslinking process. For that, the yeast’s cell wall was isolated through thermal autolysis, obtaining YMCAP_Aut (diameter: 3 - 7.5 µm; zeta potential: -13.9 mV) composed of 38 % of proteins and 41 % of carbohydrates (essentially, mannans and β-glucans). The β-glucans present in YMCAPs_Aut are constituted by glucose residues with (1→4), (1→3) and (1→6) linkages in a proportion of 50.2, 13.5 and 2.5 mol %, respectively. The (1→4) linkages are divided in (α1→4) and (β1→4). The mannans present in YMCAPs_Aut are constituted by mannose residues with (1→2), (1→3) and (1→6) linkages in a proportion of 3, 1.4 and 0.2 mol %, respectively. Through alkaline extraction using 4M KOH, the mannoproteins were solubilized and β-glucans were exposed in the microcapsule surface, obtaining YMCAPs_4M (diameter: 3 - 7.5 µm; zeta potential: 0.25 mV) composed of 34 % proteins and 54 % carbohydrates (essentially, β-glucans). The β-glucans present in YMCAPs_4M are constituted by glucose residues with (1→4), (1→3) and (1→6) linkages in a proportion of 52.8, 20.0 and 2.7 mol %, respectively. The (1→4) linkages are also divided in (α1→4) and (β1→4). YMCAPs were subsequently used for the development of a photocrosslinkable multi-YMCAPs platform. For this, YMCAPs were chemically modified with methacrylate groups or with norbornene groups. With a chemically modified surface, YMCAPs were covalently crosslinked to methacrylated gelatin (GelMA), forming a 3D multi-YMCAPs/GelMA platform with YMCAPs acting as structural/functional units, and with gelatin acting as a 3D structure for cell adhesion. Glycosidic analysis and FTIR and NMR spectroscopic confirmed the successful synthesis of functionalized YMCAPs with the different chemical groups. After, the fabricated hybrid hydrogel was applied to human adipose stem cells (hASCs) encapsulation. In vitro viability studies revealed the biocompatibility of YMCAPs when directly administered or included within the 3D matrix containing stem cells. Moreover, the potential of this hybrid hydrogel/YMCAPs platform to act as drug delivery system was explored. YMCAPs demonstrated to be an effective vehicle for hydrophobic drugs encapsulation, as observed with the use of a fluorescent molecule (e.g., Nile red) and with the use of carvacrol, antiosteoclastogenic monoterpenoid, as a medium of encapsulation of dexamethasone. Overall, the results highlight the possible use of these hybrid platform as a delivery system of stem cells and bioinstructive molecules for bone regeneration application.